Photocatalysis CO_2 reduction reaction to C_(2+) products catalyst and conversion fundamental mechanisms: A review - LIU Chang; LI Xuanzhen; WEI Yuechang* (能源环境保护)
Traditional industrial processes, especially those that rely on fossil fuels such as coal, oil and gas, result in high levels of CO_2 emissions. Capturing and utilizing CO_2 from industrial flue gas has become a top priority for reducing pollution emissions in key industries. In recent years, remarkable process in eliminating pollution and reducing CO_2 have been made. Photocatalytic CO_2 reduction technology has been widely used due to the advantages of direct use of clean solar energy resource and the moderate room temperature reaction condition. Over the past few decades, a wide variety of photocatalysts which have excellent performance have been developed. However, there is a notable research deficiency on improving the selectivity of high-value C_(2+) products. In view of the research trends and the application of new technologies, this paper describes multiple technical routes and their comparative analysis of CO utilization firstly. Then we illustrates the thermodynamic limitations, kinetic characteristics, the basic principle and mechanism of C—C coupling, the current technologies that can enhance the C_(2+) selectivity, and their existing shortcomings. Finally, we present the research process, point out the existing problems, and provide guidance for the future prospects and industrial applications of this field.